A.DABÍLOVTÍŃ «BAHADÍR» DÁSTANÍNDA FOLKLORLÍQ MOTIVLER - Allanazarov, E. (SCIENCE and SOCIETY, 2024)
In the article is analysed the using of traditional customs of folklore epic dastans,showing realistic new verge of traditional customs in creating dastan “Bahadir” by folk poet S. Nurimbetov . And also, is analysed that the given work is enriched the feelings, connected with the image of real life, with people’s friendship.